2006
DOI: 10.1523/jneurosci.4702-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Ethanol-Induced Switch of Ethanol Actions from Extrasynaptic to Synaptic Hippocampal GABAAReceptors

Abstract: Alcohol withdrawal syndrome (AWS) symptoms include hyperexcitability, anxiety, and sleep disorders. Chronic intermittent ethanol (CIE) treatment of rats with subsequent withdrawal of ethanol (EtOH) reproduced AWS symptoms in behavioral assays, which included tolerance to the sleep-inducing effect of acute EtOH and its maintained anxiolytic effect. Electrophysiological assays demonstrated a CIE-induced long-term loss of extrasynaptic GABA A receptor (GABA A R) responsiveness and a gain of synaptic GABA A R resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
192
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(217 citation statements)
references
References 73 publications
24
192
1
Order By: Relevance
“…Methods for freeze substitution and low-temperature embedding have been described previously (Wei et al, 2003;Liang et al, 2006). Briefly, cryoprotected sections were rapidly plunged into liquid propane cooled by liquid nitrogen to Ϫ190°C in a cryofixation unit (EM CPC; Leica, Wien, Austria).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods for freeze substitution and low-temperature embedding have been described previously (Wei et al, 2003;Liang et al, 2006). Briefly, cryoprotected sections were rapidly plunged into liquid propane cooled by liquid nitrogen to Ϫ190°C in a cryofixation unit (EM CPC; Leica, Wien, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrathin sections were cut on a microtome (Reichert-Jung, Vienna, Austria), picked up on nickel mesh grids that were freshly coated with a Coat-Quick "G" pen (Electron Microscopy Sciences), and air-dried at room temperature. The tissue was processed with slight modifications of the immunogold labeling methods of Matsubara et al (1996), and the current methods have been used previously for GABA A R subunit localization (Wei et al, 2003;Liang et al, 2006). Briefly, ultrathin sections were treated with 0.2% sodium hydroxide in distilled water for 5 min, and then with 0.1% sodium borohydride in 0.01 M Tris-buffered saline (TBS), pH 7.4, for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the balance between tonic and phasic inhibition may shift towards the direction of phasic inhibition during chronic ethanol consumption. Rats exposed to the CIE model of binge drinking (described later) showed a net loss of extrasynaptic, and a gain of synaptic, hippocampal GABA A receptor responsiveness to ethanol concomitant with an increase in central synaptic localization of α 4 , but not δ subunits (Liang et al, 2006). The fact that this switch corresponds with the development of tolerance to the sedating / hypnotic effects of alcohol suggests that it may be important in the pathway to addiction (Liang et al, 2006).…”
Section: Presynaptic Postsynaptic and Extrasynaptic Receptors: Phasimentioning
confidence: 97%
“…Thus, the tolerance of LAMG neuronal firing to the first dose of binge ethanol observed in the present study may be related to adaptive changes of NMDA receptors induced by CIE administration. It has been observed that chronic ethanol treatment also reduces the action of GABA (Kang et al, 1996;Faingold et al, 1998), which may involve GABA A receptor subunit alterations in the brain including the amygdala (Devaud et al, 1995;Grobin et al, 2000;Floyd et al, 2004;Liang et al, 2006). Therefore, a decrease in GABA A receptor function may also contribute to the tolerance of LAMG neuronal firing to ethanol following CIE administration.…”
Section: Discussionmentioning
confidence: 99%